Inhaled therapies targeting prostacyclin pathway in pulmonary hypertension due to COPD: systematic review - Alqarni, Abdullah A.; Aldhahir, Abdulelah M.; Bintalib, Heba M.; Alqahtani, Jaber S.; Siraj, Rayan A.; Majrshi, Mansour; AlGarni, Abdulkareem A.; Naser, Abdallah Y.; Alghamdi, Sara A.; Alwafi, Hassan (Frontiers in Medicine, 2023)
Background: Pulmonary hypertension due to chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD) is classified as group 3 pulmonary hypertension. Inhaled treprostinil, a prostaglandin I2 analogue also known as prostacyclin, has recently been approved as a first drug for patients with pulmonary hypertension secondary to ILD. However, due to a lack of evidence, no therapies are currently approved for those with COPD-associated pulmonary hypertension. Thus, this systematic review aims to summarise the current evidence to assess the impact of inhaled prostaglandin I2 analogue use on the pulmonary hemodynamics, exercise function, lung function, and gas exchange in patients with pulmonary hypertension due to COPD.We systematically searched the electronic databases of Medline, Embase, Scopus and Cochrane from inception to 1 February 2023. Studies of adult patients with a confirmed diagnosis of COPD-associated pulmonary hypertension who received inhaled drugs targeting the prostacyclin pathway were included in the systematic review. Case reports, systematic reviews, conference abstracts with no full text, non-full-text articles, non-English manuscripts and book chapters were excluded from this systematic review. A risk-of-bias assessment was carried out for the studies included in this review, using two different Cochrane risk-of-bias tools for randomised and non-randomised clinical trials.Results: A total of four studies met our inclusion criteria and were included in this systematic review.The results of one prospective clinical trial showed an improvement in the pulmonary hemodynamics (e.g., cardiac index, cardiac output and mean pulmonary artery pressure) in response to inhaled prostacyclin use in patients with pulmonary hypertension secondary to COPD. However, the severity of dyspnoea, lung function, exercise capacity and gas exchange were not affected when inhaled prostacyclin was used for patients with COPD-related pulmonary hypertension. Deleted: hemodynamic index 55 Deleted: hemodynamic index Conclusion: This systematic review demonstrated that although inhaled prostacyclin does not seem to improve COPD-related outcomes (e.g., lung function and exercise capacity), short-term use of inhaled prostacyclin has the potential to reduce mean pulmonary artery pressure and pulmonary vascular resistance without impairing ventilation-perfusion mismatch. Further studies with larger sample sizes are warranted.